Rapid Detection Of Heavy Metals On Waste-Water Polluted Soils Using Laser Induced Breakdown Spectroscopy - Heri Sugito; Ali Khumaeni; Qidir Maulana Binu Soesanto (Diponegoro University Semarang Indonesia, 2020)
The Laser Induced Breakdown Spectroscopy (LIBS) method was successfully used to detect heavy metal elements in the soil polluted by wastewater from paper mills. The study was conducted using a Nd: YAG pulse laser with a wavelength of 532 nm at 83 mJ energy and 5 torr air pressure. The laser is fired at a soil sample that has been made in the form of pellets to produce plasma. The plasma emission spectrum formed is then detected by multichannel analyzer (OMA) to obtain the emission line spectrum that represents the content of atoms and molecules in the soil sample. The spectrum detected by OMA is then compared to the standard reference spectrum at NIST (National Institute of Standards and Technology) to find out the contents of an element on a contaminated soil sample. several types of heavy metal elements Fe, Cr, Cu, Al, Cd and Mn in soils contaminated by wastewater were detected using LIBS method. Based on research results, the LIBS method is very well used for the detection of heavy metal content in polluted soils.